Priority Agricultural Commodities for Expanding and Diversifying Intra-Regional Trade in Eastern and Southern Africa - Odjo, Sunday; Fofana, Ismael; Tadesse, Getaw (AKADEMIYA2063, 2023)
This report explores the potential to diversify intra-regional trade in Eastern and Southern Africa countries (Kenya, Uganda, Ethiopia, Tanzania, Rwanda, South Sudan, Democratic Republic of the Congo, Zambia, and Burundi), with special reference to the COMESA regional market. More specifically, three critical issues were analyzed. First, the current performance and the potential to trade has been examined using several regional trade performance indicators including the production and trade similarities, and the competitiveness of the sample countries in the regional trade. The analyses revealed that there exists significant production and trade dissimilarities among the sample countries, which implies the existence of untapped potential for expanding agricultural trade in the region with tremendous consequences for smallholder producers. Second, the outlook for increasing trade and competitiveness under different policy change scenarios (reduction of cross-border trade barriers; lowering the overall cost of trading, and/or increasing productivity—crop yield) has been projected using a regional multi-commodity Market Model (ESA-EMM). This projection has indicated that the response to the policy changes and the potential for competitiveness differs across agricultural commodities and countries. Based on this deference, candidate commodities that could help countries expand their competitiveness and trade diversification have been identified. Third, the candidate commodities are prioritized based on multiple criteria that include not only regional trade potential but also the commodity’s contribution to economic growth, agricultural value addition, employment, and poverty reduction using country-level Computable General Equilibrium Model (CGE) and Micro-Simulation Models. The models simulations revealed that priority commodities that would increase the countries’ agricultural trade and other economic outcomes include both the conventional export crops such as coffee, tobacco, tea and oilseeds, and the staple crops such as maize and pulses. Maize has come out as a competitive and priority commodity for Ethiopia and Tanzania, not only to support the local food demand but also to supply for the regional market and improve the countries’ competitiveness. It was also learnt that there exists a huge potential for expanding regional trade in live animals and animal products.